Radiative properties of the skin and haircoat of cattle and other animals - Da Silva, Roberto Gomes [UNESP]; La Scala Jr., Newton [UNESP]; Tonhati, Humberto [UNESP] (My University, 2003)
Radiative properties (reflectance ρ, transmittance τ, and absorptance α) were determined for wavelengths from 300 to 850 nm in the haircoat and the skin of water buffalo, deer (Pantanal deer, Blastocerus dichotomus), and cattle of the Holstein, Simmental, Canchim, Brangus, and Nelore breeds. The results showed that white hairs have higher ρ (0.60 to 0.67) than the other coat colors, but the gray coats (mixed white and dark hair) of the Nelore cattle presented higher ρ than that of the white coats of the European breeds at wavelengths lower than 600 nm. The light gray colored skin of the Canchim cattle had higher ρ (0.66) than the non-pigmented skin of Holstein (0.53). Red skins presented ρ values higher than those of dark gray and black skins. Buffalo skin (dark gray) presented an average ρ of 0.23 ± 0.02 and α of 0.77 ± 0.02. The red haircoat of the deer presented ρ lower (0.37) than that of cattle of the same color (0.58). However, there was little difference between deer and cattle with respect to reflectance and absorptance of the skin. As for the spectral transmittance of the skin, it was very low and about the same for both species, until 600 nm. In the range 600 to 850 nm, the τ values for cattle rose to 0.17, while those for deer increased only to 0.12.
Keywords: Buffalo; Cattle; Deer; Haircoat; Pigmentation; Radiative properties; Skin; Solar radiation